Awareness about thalassemia and feasibility of cascade screening in families of thalassemia major patients - Singh, Leeha; Wade, Minal; Agrawal, Mukesh (International Journal of Contemporary Pediatrics, 2019)
Background: The main objective of this study is to assess knowledge and attitude of parents & extended relatives of children diagnosed with Thalassemia major and to evaluate feasibility of screening of extended families for thalassemia trait by correlating their willingness to get screened with actual screening. Methods: This was a cross sectional type of descriptive analytical study, conducted at the thalassemia day care center at a tertiary care teaching hospital in western India among 230 study population using a pre-designed and pre-validated structured questionnaire. Results: We found the overall knowledge score of parents about thalassemia was significantly better than relatives. About 95.83% of parents and only 31.86% of the relatives amongst the study population had adequate knowledge. Majority of study population (84.61% relatives and 100% parents) had positive attitude. The significant contributing factors for knowledge and attitude towards thalassemia were age, marital status, education level, religion and per capita monthly income. 2% relatives agreed to get themselves screened for thalassemia status out of which only 20% got themselves screened. Conclusions: This study has identified key areas which need to be highlighted and emphasized in public awareness campaigns for thalassemia screening in India.